Estoque de capital fixo no Brasil: Séries desagregadas anuais, trimestrais e mensais - José Ronaldo de Castro Souza Júnior; Felipe Moraes Cornelio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– Fixed Capital has a major role in economic growth literature and on the estimation of potential output using a production function - which is essential to design macroeconomic policy. One of the main contributions of this work, differently from the previous works, is to estimate the capital stock from a disaggregated perspective using Gross Fixed Capital Formation (GFCF) by product level throughout a detailed and historical treatment of the data from System of National Accounts (SNA). This methodology avoids distortions arise from changes in relative prices and changes in capital composition, capturing the real GFCF flows with precision and leading to better estimation of depreciation and net investment. In order to obtain a consistent and disaggregated time series of GFCF, it was necessary to adapt information from different methodologies obtained in the Supply and Uses Tables and in the Input-Output Tables (IO), as well as to use depreciation rates and life cycle in terms of products. At the end, annual estimates of the following variables were obtained for the period from 1947 to 2017: net fixed capital stock, net investment, investment rate, depreciation rate and capital/output ratio. Another contribution of this paper is the estimation of series with higher frequencies (quarterly and monthly), with data updated until 2019 and compatible with the SNA expanding the scope of application of the estimated series for short-run analysis.
Keywords: E22; 330; investment; capital stock; National Accounts